The Effectiveness of Acceptance and Commitment approach based on Self-Compassion on Psychological Well-being and Flexibility in Adolescents - Mozhdeh Hasan Sajedi; Mahdi Ghodrati Mirkouhi; Ghasem Abdollahi Boghrabadi (مطالعات روانشناختی)
The present study aimed to determine the effectiveness of acceptance and commitment approach based on self-compassion on psychological well-being and flexibility. The research design was a semi-experimental pre-test and post-test type with a control group. Statistical population included 150 girls and boys in 13 to 18 ages from the Tunkabon, Tehran, and Qazvin cities, who entered the study by online invitation. Research sample included 15 in experimental group and 15 in control group that selected through the purposive sampling. Instruments encompassed Ryff psychological well-being and Bond and et al acceptance and action questionnaire-II for psychological flexibility that completed before and after intervention in pre-test and post-test. The intervention program acceptance and commitment therapy based self-compassion was implemented in eight online 90 minutes’ sessions and control group was also placed on the waiting list.  Multivariate and univariate analysis of covariance were used to analyze of data. The results showed that the approach of acceptance and commitment based on self-compassion has been significantly effective in increasing psychological well-being and psychological flexibility. Therefore, given these findings, this approach is appropriate intervention for psychological well-being and psychological flexibility in Adolescent’s life situations.